THE STRATEGIES USED IN TRANSLATING IDIOMS FROM INDONESIAN INTO ENGLISH IN NOVEL ZIARAH - Habizar Unja (JAMBI-ENGLISH LANGUAGE TEACHING, 2019)
The obejectives of this reseach is to investigate the strategies applied by the translator in translating the Indonesian idioms in novel “Ziarah” into its English target language text “The Pilgrim” and how effectively the meaning of the ST idioms conveyed to TT using the strategies identified. In this study, the researcher employs Baker’s (2011) proposed strategies of translating idioms and Nida’s (1964) notion of equivalence in translation as the theoretical foundation for achieving the objectives of this study. Based on the results of this study, it was found that from the 28 Indonesian idioms contained in the SL text, 14 idoms were translated into English using the paraphrase stratgey, 8 idioms were translated into English by using idioms of similar meaning but dissimilar form, 5 idioms translated by using idiom of similar meaning and form, and 1 Indonesian idiom translated to English by using omission strategy. Moreover, the findings of this study also reveal that the most appropriate strategy to be used for translating Indonesian idioms into English is Baker’s (2011) strategy of translating idiom by paraphrase.